Quality Management Model (QMM) for Knowledge Resource Management in University Libraries and Information Centers: a Conceptual Framework - Sinha, Manoj Kumar; Venkata Rao, Y. (Journal of Information and Knowledge, 2008)
Quality is a relative concept, closely linked to the level of user expectation and requirements. The relative nature of quality leads ultimately to excellence. Quality management includes effectiveness and efficiency rating, cost control, service assessment, user-oriented analysis. In the University system, libraries are the backbone to support the concept of quality academic functions. Unless and until, there is a quality approach in managing knowledge resources at library, it is difficult to expect quality in academic activities in a university. In order to adapt to these new circumstances, universities are implementing new management procedures, and, for their part, university libraries are forced to make fundamental changes in order to conduct their business in line with managerial criteria. In this direction, an attempt has been made on Quality Management Model for Knowledge Resource Management and presented Assam University Library as a case study. The paper describes about the conceptual framework of Quality Management Model (QMM), objectives, steps of QMM, and impact of Quality Management (QM) on marketing concept in library and information services, QM and HRD, QM and Information Communication Technology (ICT), application of library and information services to the knowledge society.